Exploring the Correlation Between Internet Addiction, Anxiety and Achievement Test Among Iranian Male Senior High School EFL Students - Sajjadi, Seyyed Abbs (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
The rapid growth of internet usage among adolescents has raised concerns about its psychological and academic impacts. Internet addiction, characterized by excessive and uncontrolled online behavior, is increasingly linked to mental health issues such as anxiety, which may also influence academic performance. Despite growing attention globally, limited research has focused on this issue among high school EFL (English as a Foreign Language) learners in Iran. This study investigates the relationships between internet addiction, anxiety, and academic achievement among Iranian male senior high school EFL students. A sample of 70 students was randomly selected from two public high schools. Data were collected using the Zung Self-Rating Anxiety Scale (SAS, 1971), the Internet Addiction Test (IAT, Young, 1996), and a standardized academic achievement test administered by Iran’s Ministry of Education. Results revealed a significant positive correlation between internet addiction and anxiety, suggesting that higher internet use is associated with elevated anxiety levels. Additionally, both internet addiction and anxiety were negatively correlated with students’ academic achievement scores. These findings underscore the importance of monitoring students’ internet usage and addressing their mental health needs. The study contributes to the existing literature by examining this triadic relationship in a less-explored educational and cultural context.